Development of a fuzzy-fule-base system with educational applications with case study - Lee,, Kim Khoon. (Universiti Malaysia Sarawak, UNIMAS, 2009)
In criterion-referenced assessment method (CRA), total score for students’ work is gather by summing up the scores for each main criterion, where total score is overall mark awarded to student for their performed work e.g. assignment, test, project and etc. CRA is a linear assessment method where total score varies in direct proportion to the scores from each main criterion. A fuzzy inference system (FIS) based assessment model is proposed and developed to allow non-linear relationship between total score and score from each main criterion. FIS based assessment model is constructed with expert knowledge, rules collected from human expert are stored in fuzzy rule base for the use of inference. The number of rules increases exponentially as the number of main criteria increase. As a solution to this issue, a rule reduction system (RRS) is developed. The RRS can pin point a set of important rules, and it is suggested that only important rules is collected. A case study is conducted to evaluate the performance of the developed system. Empirical results show that the FIS based assessment model allow the non-linear relation among total score and the scores from each main criterion to be modeled. Besides, experiments show that the developed RRS can reduce the fuzzy rule significantly.